Delivery of siRNA targeting HIF-1α loaded chitosan modified d-α-tocopheryl polyethylene glycol 1000 succinate-b-poly(ε-caprolactone-ran-glycolide) nanoparticles into nasopharyngeal carcinoma cell to improve the therapeutic efficacy of cisplatin. Issue 44 (18th April 2016) - Lian, Daizheng; Chen, Yuhan; Xu, Gang; Zeng, Xiaowei; Li, Zhuangling; Li, Zihuang; Zhou, Yayan; Mei, Lin; Li, Xianming
Abstract : Nanoformulation of siRNA targeting HIF-1α loaded chitosan modified TPGS- b -(PCL- ran -PGA) NPs could increase the therapeutic potential of cisplatin for nasopharyngeal carcinoma. Abstract : Hypoxia inducible factor-1α (HIF-1α) related signaling pathways mediating chemoresistance has been found in various kinds of cancer, including nasopharyngeal carcinoma (NPC). In this research, a chitosan modifiedd -α-tocopheryl polyethylene glycol 1000 succinate- b -poly(ε-caprolactone- ran -glycolide) (TPGS- b -(PCL- ran -PGA)) nanoparticle (NP) was prepared for small interfering ribonucleic acid (siRNA) targeting HIF-1α delivery. The results showed that chitosan-modified TPGS- b -(PCL- ran -PGA) NPs could effectively deliver siRNA into CNE-2 cells, resulting in the decrease of HIF-1α expression and cell viability. Decreased sensitivity of cisplatin in CNE-2 cells under hypoxia condition was correlated with the overexpression of HIF-1α and multiple drug resistance gene 1 (MDR1)/P-glycoprotein (P-gp). Inhibiting HIF-1α by siRNA targeting HIF-1α loaded chitosan modified TPGS- b -(PCL- ran -PGA) NPs significantly decreased the expression of HIF-1α and MDR1/P-gp and restored the effect of cisplatin on CNE-2 cells. Moreover, synergistic anti-tumor effects could be achieved by the combined use of siRNA targeting HIF-1α loaded chitosan modified TPGS- b -(PCL- ran -PGA) NPs and cisplatin. These findings showed that the chitosan modified TPGS- b -(PCL- ran -PGA) NPs could function as an effective carrier for siRNA delivery aiming at modulating HIF-1α expression to increase the therapeutic potential of cisplatin in NPC therapy.